Mobile Tracking Membership Application on PT. LP Expedition Denpasar - Aristamy, I Gusti Ayu Agung Mas; Al Lukman, Moh Alif (Universitas Jember, 2022)
PT. LP is a company engaged in freight forwarding which currently has 3500 partners spread throughout Indonesia and one of them is in Denpasar City. Customers owned by PT. The prison located in Denpasar City currently has more than 200 people. However, because PT. LP has not utilized technology in its entire business process, causing several activities at PT. LP becomes ineffective and efficient. Customers are often confused when they want to use a pickup service and cannot find out where the package is sent, because there is no facility to track the status of the package. When the customer wants to pick up the packages, the customer must first confirm via WhatsApp to the admin, include the address where the packages are picked up and also if the customer wants to make a cashless payment, the customer must contact the admin to ask for an account number. In addition, whenever PT. LP held a promo, the information did not reach all customers. The purpose of this research is to provide a solution to these problems by building a membership tracking mobile application which will later be able to help PT. LP to simplify and speed up the process of pickup, tracking the packages, and payments. This study uses the waterfall method and chooses Android as the platform used. The results of this study are an Android-based mobile tracking application that has features of packages pickup, tracking of the packages to be picked up, providing information and promo notifications to customers, and payment features.